1
$\begingroup$

So I have a possible proof but I'm not certain it's right:

$\text{As } \frac{a_1}{x_1} + \frac{a_2}{x_2} + \frac{a_3}{x_3} \geq \frac{(a_1+a_2+a_3)^2}{x_1+x_2+x_3}\text{, we obtain } \frac{1}{a^3(b+c)} + \frac{1}{b^3(a+c)} + \frac{1}{c^3(a+b)} \geq \frac{9}{a^3(b+c) + b^3(a+c) + c^3(a+b)}$

$\begin{align} a^3(b+c) + b^3(a+c) + c^3(a+b) & = a^2(\frac{1}{b} + \frac{1}{c}) + b^2(\frac{1}{a} + \frac{1}{c}) c^2(\frac{1}{a} + \frac{1}{b}) \\ & \geq \frac{4a^2}{b+c} + \frac{4b^2}{a+c} + \frac{4c^2}{a+b} \text{ by the same inequality as above} \\ & \geq 4\frac{(a+b+c)^2}{2(a+b+c)} \text{ (same reason)} \\ & \geq 2(a+b+c) \end{align}$

Now, we have:

$\frac{1}{a^3(b+c)} + \frac{1}{b^3(a+c)} + \frac{1}{c^3(a+b)} \geq \frac{9}{2(a+b+c)}$

I'm not sure if this is a logical progression to make though. Because if $a \geq b$ then $\frac{1}{a} \leq \frac{1}{b}$, so is this not true? I feel like it must be as I can get the desired result, but I'm confused about it.

However, if this is true it is then sufficient to prove that $a+b+c \geq 3$.

$a+b+c = a+b + \frac{1}{ab} \geq 2\sqrt{ab} + \frac{1}{ab}$

It can be proved with calculus that $\forall x\ge 0,f(x) = 2\sqrt{x} + \frac{1}{x} \geq 3$. Thus the inequality is true, and the proof is finished.

Can someone please explain either why my proof is true (namely what I am confused about) or why this false proof yields the right result?

$\endgroup$
1
$\begingroup$

I think your first step gives a wrong inequality.

For the proof we can make the following thinks.

By Holder and AM-GM we obtain: $$\sum_{cyc}\frac{1}{a^3(b+c)}=\sum_{cyc}\frac{b^3c^3}{b+c}\geq\frac{(ab+ac+bc)^3}{3\sum\limits_{cyc}(b+c)}=$$ $$=\frac{(ab+ac+bc)(ab+ac+bc)^2}{6(a+b+c)}\geq\frac{3(ab+ac+bc)^2}{6(a+b+c)}=\frac{(ab+ac+bc)^2}{2abc(a+b+c)}\geq\frac{3}{2},$$ where the last inequality it's just $\sum\limits_{cyc}c^2(a-b)^2\geq0$.

Done!

$\endgroup$
  • $\begingroup$ Yeah ok, that's much more simpler than mine, thank you. However, I am still confused as to whether my proof is correct or not. Would you be able to answer that question? $\endgroup$ – Jim Jimson Apr 9 '17 at 8:35
  • $\begingroup$ @Jim Jimson I think your first step is not correct. $\endgroup$ – Michael Rozenberg Apr 9 '17 at 10:41
1
$\begingroup$

I don't think generally $\frac{a_1}{x_1} + \frac{a_2}{x_2} + \frac{a_3}{x_3} \geq \frac{(a_1+a_2+a_3)^2}{x_1+x_2+x_3}$($a_i=10$, $x_i=1$ is counterexample), it should have been$$\frac{a_1^2}{x_1} + \frac{a_2^2}{x_2} + \frac{a_3^2}{x_3} \geq \frac{(a_1+a_2+a_3)^2}{x_1+x_2+x_3}$$by Cauchy-Schwartz inequality.

And if $x<y$ then $1/x>1/y$, therefore you should calculate the upper bound of $a^3(b+c) + b^3(a+c) + c^3(a+b)$, not the lower bound.

Also, it is true that $a+b+c \ge 3$ and you can prove it much simply with AM-GM inequality: $a+b+c \ge 3\sqrt[3]{abc}=3$. However, it only proves that $\frac{9}{2(a+b+c)}\le \frac{3}{2}$, which is not what you want.

$\endgroup$
1
$\begingroup$

We have $$\sum \frac{1}{a^3(b+c)} = \sum \frac{1}{a^2(ab+ac)} = \sum\frac{(bc)^2}{ab+ca}.$$ Replacing $ab=z,bc=x,ca=y$, we need to show $$\sum\frac{x^2}{y+z}\ge\frac32,\tag1$$ for $xyz=1$.

Now (1) is trivial from C-S: $$2(x+y+z) \sum\frac{x^2}{y+z}=\sum (y+z) sum\frac{x^2}{y+z}\ge (x+y+z)^2$$ and $$x+y+z \ge 3\sqrt[3]{xyz}=3.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.